TEACHER’S CAREER PROGRESSION AND PEDAGOGY PERSPECTIVES: A SPECIAL FOCUS ON THE IMPACT OF PEDAGOGICAL TRAINING AT UNIVERSITIES IN KENYA - Ouru John Nyaegah (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The study aimed at a thorough analysis of the impact of teachers’ pedagogical training program which promotes teacher’s career progression, institutional renewal and student learning improvement at higher learning institutions in Kenya. Continuing career progression is a teacher’s formal and informal learning which leads towards his or her enhancement of skills, knowledge and personal attributes such as their attitude towards the teaching profession’s activities which are deemed necessary in carrying on with his or her professional duties successfully and effectively. The study adopted Mixed Methods Design in which a thorough evaluation of thirty-six (36) teachers’ satisfaction with the pedagogical training programs offered at their institution was done. The study discusses the training’s impact on teachers’ perceptions concerning conceptions, teaching practices and their professional development. A questionnaire whose Cronbach’s Alpha stood at 0.874 was used for data collection from respondents whose number was determined through random sampling procedure. Analysis of data was done using descriptive and inferential statistics and results indicated that participants evaluated training programs positively and thus achieved the intended learning outcomes while 85% of the total number of the respondents were implementing what they had learned and were highly satisfied with the content of the training program. Additionally, participants considered the training program as an opportunity for them to acquire new knowledge on active learning strategies and enabled them to explore different teaching strategies which could meet diverse needs of their learners and community. Besides, the researcher has identified important characteristics needed when designing a successful teachers’ pedagogical training programs in higher education and suggests that universities need to organize capacity building seminars that give special attention to the integration of technology to learning activities for teachers and administrators so that they are able to regularly coordinate, direct, and monitor instructional practices for knowledge enrichment and professional teacher development.